Reformasi Kewenangan Pengujian Peraturan Perundang-Undangan Menuju Model Ideal Negara Hukum - Rossalinda; Sarah Naziyah Latifah; Wijdan Daurut Tazakka; Utang Rosidin (ALADALAH: Jurnal Politik, Sosial, Hukum dan Humaniora, 2026)
This article examines the dualistic structure of judicial review authority between the Constitutional Court (MK) and the Supreme Court (MA) in Indonesia, which has generated legal uncertainty and inconsistent rulings. Employing a normative juridical method with statutory, conceptual, and comparative approaches, the study identifies the root causes of overlapping jurisdiction and its implications for legal coherence. The findings demonstrate that the current division of authority produces divergent review standards, an uneven judicial workload, and potential conflicts between MK and MA decisions. The study proposes an ideal model in the form of consolidating judicial review under the Constitutional Court or strengthening coordination mechanisms through the formal recognition of constitutional precedent as binding for the Supreme Court. This research contributes to ongoing debates on judicial institutional reform and offers a structured framework for redesigning Indonesia’s norm-review system to enhance legal certainty and constitutional supremacy.